Self-Efficacy among Type 2 Diabetic Patients - Dheyaa Mohammed Madran, Aqeel Habeeb Jassim, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: High level of self-efficacy and adherence to self-care activities have a positive impact on the achievement of glycemic goal among diabetic patients. In Iraq, there is a gap in knowledge related to self-efficacy management and its influence on adherence to self-care activities and overall disease control. Therefore, the study aimed to assess self-efficacy among type II diabetes mellitus and its associated socio-demographic variables. Methods: A cross-sectional study was conducted on a sample of 400 patients is selected purposively who are diagnosed with type II DM who attended AL-Zahraa Teaching Hospital in Wasit Province/ Iraq. The reliability of the questionnaire was achieved through a pilot study and then presented to experts to prove its validity. The total number of items included in the questionnaire was 34-items. The data was collected by using the semi-structured interview and analyzed by the application of descriptive and inferential statistical data analysis approach. Results: The results of the study indicated that (72.5%) of the patents exhibit a moderate self-efficacy. The analysis of variance confirmed that there were differences in self-efficacy with regards patients age (p=0.000) and duration of DM (p=0.001). Conclusions: Patients age increased age (≥70 years) and diagnosed for 5 years ago or more significantly associated with low level of self-efficacy. Self-efficacy is considered as a predisposing factor that can be deteriorated in chronic diseases like Diabetes. Increasing in self-confidence levels of diabetic patients can set the stage for glycemic control. Interventions are recommended for glycemic control of patients with longer duration of disease.